2011
DOI: 10.1007/s00439-011-1134-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies in a consanguineous family reveal a novel locus for stuttering on chromosome 16q

Abstract: Stuttering is a common neurologic disorder in children that can persist into adulthood. Although stuttering displays high heritability, Mendelian segregation typically does not occur, and linkage studies have produced limited success. A genome-wide single nucleotide polymorphism (SNP) linkage scan in a consanguineous Pakistani family followed by targeting genotyping using microsatellite markers revealed linkage on chromosome 16q. The highest linkage scores were obtained under a modified recessive model of inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 5 publications
2
32
0
1
Order By: Relevance
“…Although our evidence for linkage came from only 2 of the 43 families in our sample, we note that the majority of the remaining families were small and showed low power to detect linkage individually. Our observation of linkage in a subset of families is also consistent with previous results that have demonstrated a high degree of heterogeneity among mapped loci for this disorder (Shugart et al, 2004;Riaz et al, 2005;Suresh et al, 2006;Kang et al, 2010;Raza et al, 2010Raza et al, , 2012. Thus, it is not surprising that our study found evidence of linkage in only a subset of the families, and that the linkage locus we identified in the Brazilian population has not been previously observed for stuttering.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although our evidence for linkage came from only 2 of the 43 families in our sample, we note that the majority of the remaining families were small and showed low power to detect linkage individually. Our observation of linkage in a subset of families is also consistent with previous results that have demonstrated a high degree of heterogeneity among mapped loci for this disorder (Shugart et al, 2004;Riaz et al, 2005;Suresh et al, 2006;Kang et al, 2010;Raza et al, 2010Raza et al, , 2012. Thus, it is not surprising that our study found evidence of linkage in only a subset of the families, and that the linkage locus we identified in the Brazilian population has not been previously observed for stuttering.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the extensive evidence for genetic factors, however, the exact mode of transmission in families is not well defined, and it is unlikely to be the same in all families and populations (Alm and Risberg, 2007). For example, a number of linkage loci have been identified in consanguineous families, particularly from Pakistan (Riaz et al, 2005;Raza et al, 2010Raza et al, , 2012, while studies in outbred families in the United States have not demonstrated linkage at these loci (Shugart et al, 2004;Suresh et al, 2006). The goal of this study was to identify genetic factors underlying persistent developmental stuttering in the Brazilian population, which displays a high degree of genetic admixture, and is thus quite different from the populations used for previous genetic studies of stuttering.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage studies for persistent stuttering (see Table 1) conducted in several different populations have implicated multiple genomic loci and different modes of inheritance Raza et al 2012Raza et al , 2013Domingues et al 2014). A linkage study in a large consanguineous Pakistani family led to the identification of a linkage peak on chromosome 12 (Kang et al 2010).…”
Section: Stutteringmentioning
confidence: 99%
“…Half of the stutterers had a family history, and risk to first degree relative was 15%. Several large families with multiple individuals were affected by stuttering [10][11][12][13][14][15].…”
Section: Genetic Evidence Of Stutteringmentioning
confidence: 99%
“…These puzzling clinical features, and the fact that stuttering has its origin in the brain, hinder researchers from investigating the neural basis of stuttering. However, several genetic studies such as twin, adoption, and segregation studies have suggested that this disorder occurs by the inheritance of gene mutations [9][10][11][12][13][14][15][16]. Genetic evidence presented by several approaches, in particular, genome-wide linkage analysis have shed light on these causative genes.…”
Section: Introductionmentioning
confidence: 99%